Analysis of the Public Services Quality at the Rinding Village Head Office, Berau Regency - Zain, Moch Nur Alimi; Herdiana, Dian; Riau, Dwi Putranto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine the quality of public services at the Rinding Lurah Berau District Office. The technique for taking informants was purposive sampling, resulting in 13 informants consisting of the village head, service officers and 10 community members. The method used is descriptive qualitative, a public service dimension theory developed by Lovelock with 5 dimensions, namely tangibles, reliability, responsiveness, assurance and empathy. Based on the results of the research conducted, it was found that the Rinding Village Head Office had been able to implement several indicators in this dimension. However, there are still shortcomings, namely in terms of the comfort of the service waiting room during the day and also the need to increase the capabilities of service employees.